Here's the question you clicked on:
anonnnn
m,
you used "substitution" BTW, y= -1/2 you substituted for y in the 2nd equation you could use "elimination" y = 1/2 x - 6 or 2y = x -12 (multiply both sides by 2) or x -2y = 12 (added -2y to both sides and +12 to both sides) so your first equation in standard form is x-2y=12 1x - 2y =12 <-- multiply both sides by -2 2x + 6y = 19 after multiplying both sides (every term) by -2 you get -2x + 4y = -24 2x + 6y = 19 now add the 2 equations together term by term can you do that?
I just gave the highlights can you do y = 1/2 x - 6 becomes 2y= x-12
2y= x-12 add -2y +12 to both sides 2y-2y+12= x-12-2y+12 can you simplify
you get 12= x-2y which we can write as x-2y=12 (switching does not change anything)
you mean -2 times both sides of x-2y=12 ? -2(x-2y) = -2*12 now simplify
or should I say, "distribute" the -2 on the left and simplify on the right
first, recheck your first equation -2(x-2y) = -2*12 a minus times a minus give a plus
Last step is to replace y with -1/2 in either equation and find x